The Link between Masculinity, Alcohol and HIV/Aids in Malawi (Luviri books, 2016)
It is common knowledge that HIV is widespread in Malawi as it is in many other countries of Southern Africa. It is also a well-known fact that women suffer most and frequently are blamed the most. Many attempts are being made to address the pandemic and reduce the suffering, and often women are the focus. This book differs in that it looks at the other side, men. It contends that men have to play a major role in the fight, not only by changing behaviour but also by understanding concepts of masculinity and that women may also profit from that.